TINJAUAN KEMAMPUAN KETERAMPILAN TEKNIK DASAR PERMAINAN SEPAKBOLA SSB BINA BAKAT PEKANBARU - Rifki, Muhammad; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study was conducted to investigate the ability of basic football skills at SSB Bina Bakat Pekanbaru. This kind of research is descriptive research, in which this research is generally carried out with the main aim of systematically describing the facts and characteristics of objects or subjects that are carefully examined. The population in this study was all players of SSB Bina Bakat Pekanbaru a total of 20 people. This sampling technique is based on the total sampling technique. The sample used in this study was the SSB Bina Bakat Pekanbaru player with a total of 20 people. The results of the analysis show that the average value of the T-score skills of the Bina Bakat Pekanbaru SSB players is 46,55, which is in the range of 46-52 which means Medium.Keywords: Basic Football Technical Skills